Exposure to neonatal cigarette smoke causes durable lung changes but does not potentiate cigarette smoke–induced chronic obstructive pulmonary disease in adult mice - McGrath-Morrow, Sharon (Exp Lung Res, 2011)
The impact of early childhood cigarette smoke (CS) exposure on CS-induced chronic obstructive pulmonary disease (COPD) is unknown. This study was performed to evaluate the individual and combined effects of neonatal and adult CS exposure on lung structure, function, and gene expression in adult mice. To model a childhood CS exposure, neonatal C57/B6 mice were exposed to 14 days of CS (Neo CS). At 10 weeks of age, Neo CS and control mice were exposed to 4 months of CS. Pulmonary function tests, bronchoalveolar lavage, and lung morphometry were measured and gene expression profiling was performed on lung tissue. Mean chord lengths and lung volumes were increased in neonatal and/or adult CS-exposed mice. Differences in immune, cornified envelope protein, muscle, and erythrocyte genes were found in CS-exposed lung. Neonatal CS exposure caused durable structural and functional changes in the adult lung but did not potentiate CS-induced COPD changes. Cornified envelope protein gene expression was decreased in all CS-exposed mice, whereas myosin and erythrocyte gene expression was increased in mice exposed to both neonatal and adult CS, suggesting an adaptive response. Additional studies may be warranted to determine the utility of these genes as biomarkers of respiratory outcomes.